New trends in international marketing: Focus on branding and its connection with the consumer - Felipe, Campos Cárdenas, Luis; Consuelo, Arce González; Adolfo, Díaz Díaz, Roberto; Alejandro, Vera Calderón, José; Fernando, Naranjo Naranjo, Luis (International Journal of Innovative Research and Scientific Studies, 2025)
This article analyzes from an analytical-descriptive-documentary perspective the approach to branding and its connection with the consumer. The process of creating and managing a brand consists of achieving the positioning, recall, and recognition of the product. Currently, market conditions, globalization in its various dimensions, and fierce competition have made brand management more important in a global and interconnected world economy. Thus, it is considered that one of the main results and contributions of this research is to understand the characteristics of the consumer and achieve a positioning not only in the mind of the target market but also in the consumer's sentiment.